Missingness analysis of manufacturing systems: A case study. (August 2022) - Carbery, Caoimhe M; Woods, Roger; McAteer, Cormac; Ferguson, David M
Increasingly manufacturing companies are looking to use sensors to collect data from production lines to help analyse their performance. More rigorous approaches are needed to process and analyse the resulting data, particularly when considering missingness. In this paper, we present the results from a major study into missingness in Seagate's disc head manufacturing process in Londonderry UK. Working in collaboration with company staff, a detailed approach for analysing missingness has been developed. The work shows how missing data analytics can be employed to analyse the quality of the data, identify relationships and diagnose the presence of any patterns.